Pelatihan Penggunaan Media Pembelajaran Berbasis Teknologi Komputer - Sitorus, Zunaida; Efendi, Elfin; Putri, Seprina Aulia; Syahrani, Nadia; Fitri, Rindi Maylinda (STMIK Royal, 2024)
The rapid progress of information and communication technology today can be seen in how easy it is for people to communicate and obtain information, even in the face of limited time and space. Advances in information and communication technology are increasingly being applied to various fields and aspects of daily life to provide efficiency and convenience in handling tasks and work related to humans. One area where many people have benefited from advances in information and communication technology is education. To overcome the problems raised, the general approach that will be used in this activity is to teach computer-based media creation to teachers in elementary schools. The one-day computer-based learning media development training was carried out in a structured, patient and comprehensive manner. In general, all participants were involved in activities with strong and consistent motivation. Training as teachers and principals of certain schools to strengthen learning capacity. Teachers need to convey and minimize the results of this lesson to other teachers. Keywords: instructional media; technology; training